2019
DOI: 10.17645/si.v7i4.2328
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation and Migrant Capital in the Transnational Space: The Case of Young Kurds in France

Abstract: Transnational ties, networks, and mobilities can constitute a social resource for diaspora communities. Resources available as a result of the migration process or transnational ties can potentially become capitalised by diaspora members. Yet, diaspora members cannot automatically capitalise on all transnational networks and ties, and only resources that are mobilisable within particular transnational networks constitute “migrant capital” (Anthias, 2007; Ryan, 2011). Migrants’ children have grown up in “transn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…We can approach their transnational engagements and actions as well as mobilities as diasporic in the sense that they -at least to some extent -are connected to them having been raised in the transnational Kurdish diaspora space. Drawing from the same material as for this study, I have discussed the resources that are available to secondgeneration Kurds as a result of their parents' migration process and transnational ties elsewhere (Toivanen 2019). That article focused on the role of mobilisable resources and concluded that they were capitalised upon by second-generation members for two, albeit interrelated, aims: to advance one's educational and professional advantages and to contribute to the development of Kurdistan.…”
Section: Diasporic Circulationmentioning
confidence: 99%
See 2 more Smart Citations
“…We can approach their transnational engagements and actions as well as mobilities as diasporic in the sense that they -at least to some extent -are connected to them having been raised in the transnational Kurdish diaspora space. Drawing from the same material as for this study, I have discussed the resources that are available to secondgeneration Kurds as a result of their parents' migration process and transnational ties elsewhere (Toivanen 2019). That article focused on the role of mobilisable resources and concluded that they were capitalised upon by second-generation members for two, albeit interrelated, aims: to advance one's educational and professional advantages and to contribute to the development of Kurdistan.…”
Section: Diasporic Circulationmentioning
confidence: 99%
“…For instance, Santelli and colleagues' study on secondgeneration Algerians in France (1999) show that investment opportunities can motivate the sustaining of transnational ties to the homeland without such activities necessarily being rooted to lingering attachments and loyalties towards the homeland. I have also discussed the professional and educational reasons underlying second-generation Kurds' temporary 'return' motivations elsewhere (Toivanen 2019).…”
Section: On Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors approach migrant capital as a resource that becomes available to migrants during their migration process (Atasü-Topcuoğlu, 2019;Glorius, 2019;Hiitola, 2019) and as one that is created by migrants because of their migration (Koikkalainen, 2019;Wahlbeck & Fortelius, 2019). Migrant capital is also shown to be available to migrants' family members via their transnational ties (Dís Skaptadóttir, 2019;Saksela-Bergholm, 2019;Toivanen, 2019). Overall, migrant capital can constitute a source of community cohesion, economic advancement, informal social protection or for professional and educational gains for members of migrant communities.…”
Section: The Contributionsmentioning
confidence: 99%
“…The analysis in the articles considers both strategies and opportunities utilised by migrants and members of transnational communities in diverse economic, social and political context. As the articles show, transnational networks can be used by migrants and their family members to achieve occupational, economic and educational advantages (Atasü-Topcuoğlu, 2019;Dís Skaptadóttir, 2019;Glorius, 2019;Koikkalainen, 2019;Toivanen, 2019;Wahlbeck & Fortelius, 2019). They can also be useful in their attempts to reunite with family members (Hiitola, 2019) or to have access to informal social protection and care arrangements (Saksela-Bergholm, 2019) in both the sending and receiving societies.…”
Section: The Contributionsmentioning
confidence: 99%